The Dimensions Of The Fraud Pentagon In Academic Fraud Behavior: A Case Study Of Accounting Students At Brawijaya University - Dhandi Fahriza; Ayu Fury Puspita (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to analyze the influence of the fraud pentagon on students' academic dishonesty behavior using a quantitative approach on 100 accounting students at Brawijaya University. The data collection technique was conducted through questionnaire distribution using the purposive sampling method. The data analysis technique employed was multiple linear regression analysis with the assistance of SPSS 27. The results of this study indicate that the variables of pressure, opportunity, rationalization, and capability have a significant effect on students' academic dishonesty behavior. In contrast, arrogance does not have a significant effect. This is evidenced by the t-test, where the significance value of arrogance is 0.058. These findings support the application of the Fraud Pentagon Theory in an academic context, providing important implications for educational ethics policies.